The Implementation of Personal Letter in Teaching Writing of Narrative Texts to the Eighth Graders of SMP Negeri 5 Sidoarjo (RETAIN, 2013)
Abstract Writing is one of the four language skills which have to be mastered in language learning, especially English. It is a productive skill in which the students produce the language in the written form. Most of the students think that writing is the most difficult skill. It is because they need some processes to be done. Narrative text is a genre text that is taught in Junior High School. This text is considered as an important text since it arises every year from Junior High School until Senior High School except expository text. Using personal letter as an activity can be use to help the students in writing narrative texts. This study are to describe how is the personal letter activity implemented in teaching writing of narrative texts to the eighth grades, to describe how the students’ writing tasks after the personal letter is implemented as an activity, and to find out the students’ responses are toward the personal letter activity in teaching writing of narrative texts. This research is a descriptive qualitative research. The subject of the study is the eighth grades. The instruments of this study are semi – structured observation, students’ writing tasks and questionnaire. The instruments are used to gain the data. The data are collected and analyzed by doing observation during the teaching learning process. The semi – structured observation and questionnaire were used to describe the implementation of personal letter as an activity in teaching writing of narrative texts. And, the students’ writing tasks are used to know the students’ writing abilities in narrative texts. Based on the research conducted by the researcher, the results showed that writing of the students were better after using personal letter as the activity in writing narrative texts. In conclusion, personal letter can be used as an activity to teach writing of narrative texts. It is because this activity can help the students to organize, to generate, and to write their ideas of writing narrative texts, so they can write the narrative texts well. Keywords: Writing, Narrative text, Personal letter